Los hospitales de la sierra tarasca en el siglo XVII; su importancia urbano-arquitectónica - Gutiérrez Equihua, Ángel (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The present work contains a study of the important hospitals of the Immaculate Conception in the 17 th century Tarascan Sierra, a mountainous region in the center of the State of Michoacán (West Mexico). It focuses especially on the parishes of Aranza, Sevina, and Capacuaro, all geographically connected and among the few wich at that time were administered by the secular clergy. The analysis comprehends three mayor elements: 1) the origins of the hospitals, 2) an historical reconstruction of the institution, and 3) its architectonical characteristics and role in the development of urban structures. This multidisciplinary research is based on the consultation and confrontation of primary and secondary written sources, iconographic material, oral tradition, and the urban structure of the present day villages, including a profound study of the hospital’s constructions and organizations that survived the sands of time. The principal objective is not only to show the historical importance of the institution in the case of the mentioned indigenous villages in the Sierra but also to contribute to the highly necessary documentation and conservation of the buildings, organizations and related traditions that have survived until today and that form part of the rich and diverse historical and cultural patrimonies of Mexico.

El presente trabajo contiene los resultados de una investigación urbano- arquitectónica acerca de los hospitales de La Inmaculada Concepción de La Sierra tarasca, haciendo énfasis en el siglo XVII, una región montañosa del centro del estado de Michoacán, que se encuentra ubicado al occidente de México. El estudio está enfocado a los asentamientos existentes hasta hoy, que durante aquella centuria pertenecieron a las parroquias de Aranza, Sevina y Capacuaro, los cuales aparte de ser administrados ya desde aquel tiempo por el clero secular, conforman una zona geográfica y culturalmente homogénea. El análisis comprende tres partes: en la primera, se buscan los orígenes de los hospitales; en la segunda, se hace una reconstrucción histórica de la institución en cada sitio; y en la tercera, se exponen las características arquitectónicas de sus edificios y su importancia para el desarrollo de las estructuras urbanas de cada lugar. El trabajo se desarrolló en base a la consulta de fuentes escritas, imágenes y la tradición oral, las cuales fueron confrontadas con el testimonio histórico que nos proporciona la lectura de los vestigios materiales de los propios hospitales y asentamientos existentes hasta hoy en la zona en estudio.
Facultad de Arquitectura. Maestría en Arquitectura, Investigación y Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-M-2007-0004; Hospitales; Sierra tarasca; Aranza; Sevina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1550